2013
DOI: 10.1159/000353568
|View full text |Cite
|
Sign up to set email alerts
|

Y-39983, a Selective Rho-Kinase Inhibitor, Attenuates Experimental Autoimmune Encephalomyelitis via Inhibition of Demyelination

Abstract: Objective: Rho-associated kinase (ROCK) is a serine/threonine kinase and a major downstream effector of the small GTP-binding protein, Rho. Rho-ROCK triggers an intracellular signaling cascade that controls actin cytoskeleton and is essential for cell motility and adhesion, neurite outgrowth and retraction. In chronic disabling disease, multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE), demyelination and axonal damage are the major pathological changes contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Our data also showed similar results, indicating that NogoA, NgR, and RhoA mRNA and protein increased in the brains and/or spinal cords of rats during the acute and/or remission stages. In contrast, NogoA-knockout or -knockdown mice developed a milder disease course of EAE (Karnezis et al, 2004;Yang et al, 2010), and RhoA inhibitors have been shown to attenuate the progression of EAE (Gao et al, 2013). However, despite all of these advances in MS research, the neuroprotective treatment of MS is still a major challenge in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed similar results, indicating that NogoA, NgR, and RhoA mRNA and protein increased in the brains and/or spinal cords of rats during the acute and/or remission stages. In contrast, NogoA-knockout or -knockdown mice developed a milder disease course of EAE (Karnezis et al, 2004;Yang et al, 2010), and RhoA inhibitors have been shown to attenuate the progression of EAE (Gao et al, 2013). However, despite all of these advances in MS research, the neuroprotective treatment of MS is still a major challenge in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with ROCK inhibitor Y-39983, a more potent derivative of Y-27632, revealed a faster recovery from disease, decreased clinical symptoms, decreased inflammatory lesions, and decreased demyelination. This treatment led to an increase in myelinated axons and an increased complete recovery in MS model mice with experimental autoimmune encephalomyelitis or EAE (Gao et al, 2013 ).…”
Section: Als and Spinal Muscular Atrophy (Sma)mentioning
confidence: 99%
“…ROCK is a serine/threonine kinase and a key regulator in controlling formation of the actin cytoskeleton, as well as cell motility, and cell adhesion. Selective ROCK inhibitors, such as FSD-C10 or Y-39983, have been shown to exhibit therapeutic potential in an EAE model via attenuation of demyelination and neuroinflammation (Gao et al, 2013; Li et al, 2014). More recently, microglial treatment with a ROCK inhibitor Fasudil induced alteration in microglial phenotype polarization and functional plasticity, shifting the M1 to a M2 phenotype (Chen et al, 2014a).…”
Section: Pharmacological Approaches For Modulating Microglial Phenotypesmentioning
confidence: 99%